2019
DOI: 10.1037/xlm0000643
|View full text |Cite
|
Sign up to set email alerts
|

Representation and selection of determiners with phonological variants.

Abstract: The aim of this study is to contribute to a better understanding of cross-linguistic differences in the time course of determiner selection during language production. In Germanic languages, participants are slower at naming a picture using a determiner + noun utterance (die Katze "the cat") when a superimposed distractor is of a different gender (gender congruency effect). In Romance languages in which the pronunciation of the determiner also depends on the phonology of the next word, there is no such effect.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Whereas the sample for the lab experiment mostly consisted of undergraduate students with backgrounds in linguistics or psychology, the background of participants in the on-line study was more diverse. The two populations might differ in the strategies they used to perform the task, in the extent to which they noticed the similarities between distractors and target words, in their ability to ignore the distractor, or in the relative speed with which they processed the two words (Bürki et al, 2019;Bürki & Madec, 2022). It is important to note, however, that this nding cannot be generalized to other paradigms or effects without further investigation.…”
Section: Discussionmentioning
confidence: 94%
“…Whereas the sample for the lab experiment mostly consisted of undergraduate students with backgrounds in linguistics or psychology, the background of participants in the on-line study was more diverse. The two populations might differ in the strategies they used to perform the task, in the extent to which they noticed the similarities between distractors and target words, in their ability to ignore the distractor, or in the relative speed with which they processed the two words (Bürki et al, 2019;Bürki & Madec, 2022). It is important to note, however, that this nding cannot be generalized to other paradigms or effects without further investigation.…”
Section: Discussionmentioning
confidence: 94%
“…Before concluding, we highlight the methodological implications of the present findings. While the majority of picture–word interference studies report comparisons involving the same list of distractors counterbalanced across conditions, not all of them do (e.g., Bürki et al, 2019; Finkbeiner & Caramazza, 2006; Foucart et al, 2010; Mahon et al, 2007; Rizio et al, 2017). The finding that naming latencies are influenced by word length and by orthographic neighbourhood (see Supplementary Material 3) calls for a strict control of these properties if different distractor lists are to be used.…”
Section: Discussionmentioning
confidence: 99%
“…The close inspection revealed that from a total of 193 works, only 12 did not mix animate and inanimate stimuli randomly within the target and distractor pairs and the experimental conditions (Ehri, 1976;Guttentag and Haith, 1979;Schnur et al, 2006;Foucart et al, 2010;Muehlhaus et al, 2013;Hwang and Kaiser, 2014;Dank and Deutsch, 2015;DiBattista, 2015;Shin, 2016;Bürki et al, 2019;Deutsch and Dank, 2019;Sá-Leite et al, 2021). Additionally, among these 12, only three of them explicitly stated that they controlled animacy (Foucart et al, 2010;Shin, 2016;Bürki et al, 2019;i.e., "only inanimate stimuli were used") and only one included animacy as a factor to check its impact on the effect sizes (Sá-Leite et al, 2021). Importantly, only Shin (2016) and Sá-Leite et al ( 2021) explicitly mention and discuss animacy theoretically as a potential factor affecting the results.…”
Section: Summary and Description Of The Studiesmentioning
confidence: 99%
“…However, the most ingenious element of the PWI paradigm, i.e., the use of language comprehension to study language production in its oral and written form (Bonin and Fayol, 2000;Bürki et al, 2019), involves a complex process whose outcomes can be misleading. In the PWI paradigm trials consist of a target that is both a picture and a noun, along with a written or oral distractor noun.…”
Section: Introductionmentioning
confidence: 99%